FPGA Based Step Motor Control for Solar Panels - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This work demonstrates the application and operation principle of a stepper motor to enable the rotation of solar panels using an FPGA-based Basys3 circuit board coded with the Very High Speed Integrated Circuit Hardware Description Language (VHDL). Step motors are used for the solar panels to follow the sun both vertically (Elevation) and horizontally (Azimuth). The calculation actualized on FPGA permits a considerable abatement of the equal preparing time created by various speed controllers. Speed control of the system was made using VHDL code, Register Transfer Level (RTL) digital hardware structure was created with this code block. To obtain delayed pulse duration applied to the motor, the 50 MHz oscillator frequency provided by the Basys-3 card is divided into lower frequencies ranging from 2 to 10 ms [1] [2]. In this case, the angle of rotation, direction and speed of the motor changes according to the position of the sun. The biggest advantage of using FPGAs instead of a discrete digital component (micro-controllers with active components) in such applications is that they are made very fast and coarse changes during design and that the whole design is achieved as a single buried system. The total programmable hardware structure (utilization of FPGA capacity) used for this project is almost 5% of the total source. All framework takes a shot at an inserted framework without a PC interface. © 2019 IEEE.
Keywords: basys-3; embedded system; FPGA; solar panel; step motor; VHDL